Development of ceramic extruder for three dimensional printing - Lim, Chun Yong (2022)
Direct ink writing (DIW) 3D printer is one of the additive manufacturing techniques. It is an extrusion based additive manufacturing method, whereby the feedstock is dispensed out of a nozzle under controll platform and hence threeable flow rate condition. The feedstock is then de dimensional structure is built layerbylayer posited on the (Lewis et al., 2006) Nowadays, the type of 3D printers available in the marke t . are mainly fused deposition modelling (FDM) 3D printers and stereolithography (SLA) 3D printer which uses polymer filament or resin. However, direct ink writing 3D printer are not commonly available in the market. The purpose of this research is to devel op a ceramic extruder which can be integrated to existing fused deposition modelling (FDM) 3D printers. Besides that, the extrudability of ceramic feedstock and its printability under the present extruder system are investigated. The development of extrude r includes design of extruder geometries, extruder nozzle and materials classification for the design extruder to operate. After the extruder prototype is fabricated, the operation of extruder is analysed. Depending on the quality of printed object, the ex finetruder is tuned so that the best printed quality of product is achieved. The extruder is then attached to existing FDM 3D printer and tested on the synchronization of the extruder with 3D printer movement.